2019
DOI: 10.1097/mcg.0000000000001187
|View full text |Cite
|
Sign up to set email alerts
|

More Severe Deficits in Performance Status at Time of Liver Transplant is Associated With Significantly Higher Risk of Death Following Liver Transplantation

Abstract: Goal: To evaluate the impact of Karnofsky Performance Status score (KPSS) at the time of liver transplantation (LT) on post-LT survival. Background: While the Model for End-Stage Liver Disease (MELD) score is used to prioritize individuals for LT, it does not specifically incorporate functional status into patient assessment for LT. Methods: Using 2005 to 2016 United Network for Organ Sharing data, all adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Thus our observation of the association between poor performance status and higher odds of decompensating events, may simply reflect that underlying worsening of liver disease, which leads to development of decompensation and complications itself drives the gradual decline in performance status. Furthermore, although our present study focuses specifically on waitlist outcomes, previously studies have demonstrated that worse FS also correlates with lower survival after LT. 29 For its strengths, the study assesses a large, national, diverse patient population over 12 years and uses a frailty instrument commonly and inexpensively used across specialties, including oncology, thereby providing a common framework for multidisciplinary care as transplant evaluation often involves. Among its limitations, the crosssectional design of the study precludes establishment of causality.…”
Section: Discussionmentioning
confidence: 99%
“…Thus our observation of the association between poor performance status and higher odds of decompensating events, may simply reflect that underlying worsening of liver disease, which leads to development of decompensation and complications itself drives the gradual decline in performance status. Furthermore, although our present study focuses specifically on waitlist outcomes, previously studies have demonstrated that worse FS also correlates with lower survival after LT. 29 For its strengths, the study assesses a large, national, diverse patient population over 12 years and uses a frailty instrument commonly and inexpensively used across specialties, including oncology, thereby providing a common framework for multidisciplinary care as transplant evaluation often involves. Among its limitations, the crosssectional design of the study precludes establishment of causality.…”
Section: Discussionmentioning
confidence: 99%
“…( 3,4 ) Frailty is present in 18% to 25% of patients with end‐stage liver disease (ESLD), and it is associated with nearly twice the mortality of reference populations as well as increased hospital admission, waitlist mortality, posttransplant complications, and health care costs. ( 3,5‐7 ) Frailty is also a progressive condition for patients on the waiting list as its prevalence doubles from the time of listing to the time of LT. ( 8,9 )…”
mentioning
confidence: 99%
“…(C) Poor performance on the KPS and ADL is associated with significantly higher mortality before LT; poor performance on the ECOG is associated with significantly higher mortality after LT. Adapted from Tandon et al, ( 5 ) McCabe et al, ( 7 ) Jacob et al, ( 12 ) and Tapper et al ( 16 ) KPS, Karnofsky performance status; R, reliant on others; SC, able to perform self‐care.…”
Section: Measures Of Physiologic Reservementioning
confidence: 99%
“…In patients awaiting LT, a lower KPS score is associated with the increased prevalence and severity of ascites and encephalopathy. ( 7 ) Those in the KPS B (hazard ratio [HR], 1.14) and KPS C categories (HR, 1.63) had an increased risk of mortality when compared with those in the KPS A category. ( 6 ) Those with lower KPS scores after LT are more likely to have a longer length of stay (LOS), require readmissions, ( 7 ) and need longer intubation time.…”
Section: Measures Of Physiologic Reservementioning
confidence: 99%
See 1 more Smart Citation